Economic inequality : the American dream under siege - Frazer, Coral Celeste (Twenty-First Century Books, 2018)
Examines the economic gap between the rich and the poor in the United States. Highlights solutions that could help close the gap and make the American dream possible for everyone. Includes tables, graphs, a glossary, and color photographs.